Spatial Data Identifying Strategic Reserves in Oregon extquotesingles Forests for Biodiversity, Water, and Carbon to Mitigate and Adapt to Climate Change - Logan T Berner; Beverly E Law (PANGAEA, 2022)
To support local to regional climate change mitigation and adaptation actions, this spatial dataset prioritizes forestlands for preservation across Oregon, United States. The urgent need for climate change mitigation and adaptation actions has led to efforts to protect 30% of land area by 2030 (30x30) and 50% by 2050 (50x50). A key aspect of these efforts is strategically prioritizing lands for new protection, so they most effectively protect climate and biodiversity. Oregon has among the most carbon-rich forests on the planet, yet only about 10% of it extquotesingles forests are currently protected, which is lower than any other state in the western United States. We therefore developed and applied a quantitative forest preservation priority ranking system that incorporated existing statewide spatial datasets related to forest carbon, biodiversity, and climate change resilience. Specifically, this approach utilized estimates of (1) tree aboveground carbon stocks, (2) tree, amphibian, bird, mammal, and reptile species richness, and (3) climate change resilience derived from metrics of topoclimatic diversity and landscape connectivity. Input datasets reflect contemporary (2000-2020) forest conditions and were re-gridded to a common 30 m x 30 m spatial resolution. Each forest patch (i.e., a 30 x 30 m grid cell) was ranked relative to others in its ecoregion based on carbon, biodiversity, and/or resilience metrics (i.e., four prioritization scenarios). The extent of currently protected (GAP 1 or 2; IUCN Ia-VI) forestlands was determined for each ecoregion and then the highest-ranked unprotected forestlands were identified that could be preserved to meet the 30x30 and 50x50 targets using each prioritization scenario. This spatial dataset therefore identifies the locations of forestlands that could be strategically preserved to meet the 30x30 and 50x50 targets as prioritized using each of the four scenarios. Each raster covers forestlands across Oregon at 30 m x 30 m spatial resolution and is provided in GeoTiff format using an Albers Equal Area projection. These spatial data were produced by Law et al. (2022) and support efforts to preserve Oregon extquotesingles forests for climate change mitigation and adaptation.